2015
DOI: 10.1002/pssb.201552559
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and intermediate‐range order in amorphous GeTe

Abstract: We have investigated amorphous GeTe by anomalous X‐ray scattering coupled with reverse Monte Carlo modeling. Experiments were conducted at the two K‐absorption edges in order to determine differential structure factors for both elements. The results indicate that simple models like the 8−N bonding rule cannot accurately rationalize the atomic structure. Te atoms are found to be over‐coordinated with a mean coordination number of about 2.5. Moreover, evidence is given for a high level of intermediate‐range orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 36 publications
(59 reference statements)
10
33
0
Order By: Relevance
“…[34]. These were found to reproduce very accurately the measured pair-correlation functions and structure factors for somewhat different compositions [29,[48][49][50]. Molecular dynamics (MD) simulations of Car-Parrinello type (CPMD code) were performed on a 200atom system in a cubic box with periodic boundary conditions and a density equal to experimental ones (0.0337Å…”
Section: Simulation Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…[34]. These were found to reproduce very accurately the measured pair-correlation functions and structure factors for somewhat different compositions [29,[48][49][50]. Molecular dynamics (MD) simulations of Car-Parrinello type (CPMD code) were performed on a 200atom system in a cubic box with periodic boundary conditions and a density equal to experimental ones (0.0337Å…”
Section: Simulation Methodsmentioning
confidence: 98%
“…Three amorphous models were obtained by quenching previously equilibrated liquids obtained at 820 K following a TABLE I. Elaboration and investigation characteristics of GeTe amorphous films studied by different research groups [29,[48][49][50]. The information marked with an asterisk (*) corresponds to deposition of Ge-Sb-Te amorphous films performed by the group of Yamada and Matsunaga [51].…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some early studies suggested the so called 3-3 model (both Ge and Te are threefold coordinated) but later the 4-2 model became prevailing. However, some recent works raised doubts about the validity of the 8-N rule [9][10][11]. The precise determination of the coordination numbers of Ge and Te in amorphous Ge-Te alloys is a rather difficult task.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different scattering laws of the same substance are often employed. Such functions may be available from neutron scattering using isotopic substitution techniques [11][12][13] or from anomalous x-ray scattering [12,14,15]. Another strong constraint exists if known significant structural correlations exist between certain atoms in the sample as is the case in disordered materials made up of molecular units.…”
Section: Introductionmentioning
confidence: 99%